Management of non traumatic surgical emergencies during the COVID-19 pandemia - PARREIRA,JOSÉ GUSTAVO (2020)
ABSTRACT In December 2019, in Wuhan, China, the first cases of what would be known as COVID-19, a disease caused by an RNA virus called SARS-CoV-2, were described. Its spread was rapid and wide, leading the World Health Organization to declare a pandemic in March 2020. The disease has distinct clinical presentations, from asymptomatic to critical cases, with high lethality. Parallel to this, patients with non-traumatic surgical emergencies, such as acute appendicitis and cholecystitis, continue to be treated at the emergency services. In this regard, there were several doubts on how to approach these cases, among them: how to quickly identify the patient with COVID-19, what is the impact of the abdominal surgical disease and its treatment on the evolution of patients with COVID-19, in addition to the discussion about the role of the non-operative treatment for abdominal disease under these circumstances. In this review, we discuss these problems based on the available evidence.